The Riddle of Style Changes in the Visual Arts after Interference with the Right Brain - Blanke, Olaf; Pasqualini, Isabella (Frontiers in Human Neuroscience, 2012)
We here analyze the paintings and films of several visual artists, who suffered from a well-defined neuropsychological deficit, visuo-spatial hemineglect, following vascular stroke to the right brain. In our analysis we focus in particular on the oeuvre of Lovis Corinth and Luchino Visconti as both major artists continued to be highly productive over many years after their right brain damage. We analyzed their post-stroke paintings and films, indicate several aspects that differ from their pre-stroke work (omissions, use of color, perseveration, deformation), and propose–although both artists come from different times, countries, genres, and styles–that their post-stroke oeuvre reveals important similarities in style. We argue that these changes may be associated with visuo-spatial hemineglect and the right brain. We discuss future avenues of how the neuropsychological investigation of visual artists with and without neglect may allow us to investigate the relationship between brain and art.